Triangular relationship between single nucleotide polymorphisms in the CYP2R1 gene (rs10741657 and rs12794714), 25-hydroxyvitamin d levels, and coronary artery disease incidence - Hassanein, Sally I.; Abu El Maaty, Mohamed A.; Sleem, Hameis M.; Gad, Mohamed Z. (Biomarkers, 2014)
Objective: To investigate the relationship between the rs10741657 and rs12794714 polymorphisms in the CYP2R1 gene, 25(OH)D levels, and coronary artery disease (CAD) incidence.Methods: In total, 134 male patients with verified CAD were recruited, alongside 109 age- and sex-matched controls. Genotyping was performed by polymerase chain reaction-restriction fragment length polymorphism, using the corresponding restriction enzyme for each polymorphism, whereas 25(OH)D levels were analyzed by HPLC-UV.Results: 25(OH)D levels were significantly lower in patients. The genotypic and allelic distributions of the rs10741657 polymorphism were significantly different between patients and controls, whereas insignificant results were obtained for the rs12794714 polymorphism. Furthermore, rs10741657, but not rs12794714, predicted 25(OH)D levels.Conclusion: The rs10741657 polymorphism is a novel genetic marker for CAD.
Gesehen am 16.09.2020